GAMBARAN SOSIO BUDAYA GIZI ETNIK MADURA DAN KEJADIAN STUNTING BALITA USIA 24–59 BULAN DI BANGKALAN - Rizki Kurnia Illahi; Lailatul Muniroh (Universitas Airlangga, 2016)
Stunting is a nutritional problems in Indonesia. District with the highest prevalence of stunting in East Java in 2015 was Bangkalan. Madurese peoples is known to have socio cultural practices which related to nutrition. This study was aimed to describe s ocio-cultural aspects of nutrition that related to s tunting. This study was a descriptive study with cross sectional design. The study was done in Ujung Piring Village, Bangkalan and the sample size was 62 children who were selected by using simple random sampling technique. Stunting status was assessed through anthropometric indicators according to height for age (H/A) and compared to WHO-MGRS standard. Data on practices of socio culture in nutrition during pregnancy and childbirth, breastfeeding and children under-ﬁ ve, were collected through interviews. Data were analyzed descriptively. The results showed that the prevalence of s tunting in children under ﬁ ve in Ujung Piring Village was 29%. Practices of socio culture in nutrition on Madurese Ethnic including socio culture in nutrition of mother and socio culture in nutrition of toddler. Socio cultural aspect of nutrition which probably related to s tunting were food taboo for pregnant women, prelacteal food for newborn, infants did not receive immunization and early giving of complementary feeding. It is suggested to have an effort to decrease food taboo for pregnant women, reduce prelacteal food for newborns, and reduce giving complementary feeding early through counseling involving parent’s mothers as the key person in health communication.